Effects of royal jelly consumption on clinical outcomes in patients with ischemic stroke: A triple-blind randomized controlled trial - Elham Karimi; Arman Arab; Fariborz Khorvash; Maryam Kazemi; Reza Amani (Journal of Functional Foods)
The therapeutic impact of royal jelly (RJ) consumption in patients with ischemic stroke is unknown. Therefore, we conducted a randomized, triple-blind, placebo-controlled clinical trial to evaluate the role of RJ supplementation on clinical and biochemical outcomes in patients recovering from ischemic stroke. Out of 64 enrolled patients (45–80 yrs.) with ischemic stroke, 32 were randomized to the RJ group and 32 to the placebo (control) group. Groups completed a 12-week intervention. The intervention group received 1000 mg/d of RJ dragee after breakfast. We evaluated stroke-related disability, quality of life, and inflammatory and oxidative stress markers at baseline and post-intervention. At post-intervention, serum levels of erythrocyte sedimentation rate decreased in the RJ group compared to the control group (adjusted mean difference, −8.65 mm/h [95 % CI, −14.75 to −2.55]). Additionally, serum nitric oxide levels increased in the RJ group (adjusted mean difference, 10.18 nmol/mL [95 % CI, 0.51 to 19.86]) post-intervention compared to the control group. Furthermore, the RJ group exhibited a decreased oxidative status index (adjusted mean difference, −0.003 [95 % CI, −0.006 to −0.0001]) and reduced odds of stroke-related disability (adjusted odds ratio, 0.20 [95 % CI, 0.05 to 0.70]) compared to the placebo group. Moreover, RJ supplementation improved the quality-of-life measures in the RJ group (adjusted mean difference, 16.64 [95 % CI, 1.17 to 32.12]) compared to the control group. Our findings reflect the potential benefits of RJ consumption on clinical and biochemical outcomes of patients recovering from ischemic stroke. Importantly, we acknowledge the necessity of additional studies to verify the efficacy of RJ supplementation in patients recovering from strokes. Trial registration: Iranian Registry of Clinical Trials (IRCT20180818040827N4), registered on October 9, 2021; https://www.irct.ir/trial/59275